We assume you want to find the inverse transform of s/(s^2 +3s -4). This can be written in partial fraction form as
(4/5)/(s+4) + (1/5)/(s-1)
which can be found in a table of transforms to be the transform of
(4/5)e^(-4t) + (1/5)e^t
_____
There are a number of ways to determine the partial fractions. They all start with factoring the denominator.
s^2 +3x -4 = (s+4)(s-1)
After that, you can postulate the final form and determine the values of the coefficients that make it so. For example:
A/(s+4) + B/(s-1) = ((A+B)s + (4B-A))/(s^2 +3x -4)
This gives rise to two equations:
(A+B) = 1
(4B-A) = 0
24= 3*2^3
88= 11*2^3
664= 83*2^3 -> 83=11+72 = 11 + 2^3*3^2
664=2^3 (11+2^3*3^2) = 88 +(2^3*2^3*3^2) = 88 +(24^2)
8408= 1051 * 2^3 -> 1051= 83+968 -> 968 = 2^3 * 11^2
8408= 2^3 (83+2^3*11^2) = 664 +(2^3*2^3*11^2) = 664 +(88^2)
So:
a(n) = a(n-1) + a(n-2)^2
Lets check: 88+24^2= 664
664+88^2= 8408
1 + 54 = 55
2 + 53 = 55
3 + 52 = 55
4 + 51 = 55
5 + 50 = 55
6 + 49 = 55
7 + 48 = 55
8 + 47 = 55
9 + 46 = 55
10 + 45 = 55
and so on...
I hope that helps. :)
C is the answer because there is no variable for X which without it would make a horizontal line.